ASH2L is involved in promotion of endometrial cancer progression via upregulation of PAX2 transcription. Issue 6 (23rd May 2020) - Zeng, Kai; Wu, Yi; Wang, Chunyu; Wang, Shengli; Sun, Hongmiao; Zou, Renlong; Sun, Ge; Song, Huijuan; Liu, Wei; Sun, Ning; Wei, Shan; Liu, Wensu; et al.
Abstract: Absent, small or homeotic 2‐like protein (ASH2L) is a core component of a multimeric histone methyltransferase complex that is involved in the maintenance of active transcription, participating in several cancers, however the biological function and molecular mechanism of ASH2L in endometrial cancer (ECa) are largely unknown. Endometrial cancer is a common malignant tumor in women and the incidence of this cancer is on the rise. Estrogen‐ERα signaling, as an oncogenic pathway, plays a crucial role in endometrial carcinogenesis. Therefore, further exploration of the molecular mechanisms around ERα‐mediated gene transcription in ECa would be helpful to the understanding of tumor development and to finding a new therapeutic target for ECa. Here, our study demonstrated that ASH2L was highly expressed in ECa samples, and higher expression of ASH2L was positively correlated with a poor prognosis. Moreover, we identified that ASH2L associated with ERα and that knockdown of ASH2L resulted in decreased expression of a subset of the estrogen‐induced target genes, including paired box 2 ( PAX2 ), an oncogenic gene in ECa. ASH2L was recruited to cis ‐regulatory elements in PAX2, thereby altering histone H3K4me3 and H3K27me3 levels, to enhance ERα‐mediated transactivation. Finally, depletion of ASH2L suppressed endometrial cancer cell proliferation and migration. Our findings suggest that ASH2L participates in the promotion of ECa progression, if not totally at least partially, via upregulation of PAX2 transcription. Abstract : Expression of ASH2L was positively correlated with a poor prognosis in endometrial cancer. ASH2L enhanced ERα‐mediated transactivation and knockdown of ASH2L resulted in decreased expression of PAX2 by altering histone H3K4me3 and H3K27me3 levels and recruitment of ERα. Depletion of ASH2L suppressed endometrial cancer cell proliferation and migration.